Promoting integrated STEM education among students via fabrication of interactive exhibit - Tan, Yong Leng Kelvin; Subramaniam, R. (Frontiers in Education, 2024)
Few studies in the education literature have focused on integrated STEM in a comprehensive manner and, even among these, there does not seem to be a significant emphasis on all the four disciplines. In addition, there are hardly any studies that focus on transitioning across prototype variants to demonstrate students' understanding of what they must grapple with, including STEM concepts while coming up with a product. This qualitative study explored how a group of high school students harnessed the constituent disciplines of STEM to fabricate an interactive exhibit on laminar flow in an iterative manner. It was found that in the process of prototyping a working model of the exhibit, the students were able to demonstrate a working understanding of 35 relevant concepts in the four STEM disciplines, with science (13) and engineering (12) predominating, followed by mathematics (5) and technology (5). The students were able to incorporate four levels of interactivity in the exhibit, and this allowed visitors to explore the factors affecting laminar flow in the exhibit during a public exhibition in the school. Examination of the STEM dispositions of the students indicated a positive influence as a result of the activity. To the best of our knowledge, this study has incorporated the highest number of STEM concepts. We argue for the need for more studies that integrate all the four constituent disciplines of STEM in promoting integrated STEM education.